Czech congress of pediatric surgery with international participation : Prague, Czech Republic : May 28-30, 1998 (Galén, 1998)
Příspěvky, přednesené r. 1998 na lékařském kongresu v Praze s mezinárodní účastí, řeší problémy z oboru dětské chirurgie.
Keywords: chirurgie; Child; Infant; dítě; General Surgery; kojenec; pediatrie